Effects of Cataract Surgery on Intraocular Pressure in Patients with and without Glaucoma - Tülin İsmi; Ayça Yılmaz (Türk Oftalmoloji Dergisi, 2013)
Pur po se: To evaluate the effects of phacoemulsification surgery with primary intraocular lens (IOL) implantation on intraocular pressure (IOP) in various types of glaucoma patients with visually significant cataract and to compare these results with cataract patients without glaucoma. Ma te ri al and Met hod: This retrospective study included consecutive cases of 21 primary open-angle glaucoma patients, 13 primary angle-closure glaucoma (PACG) patients, 11 pseudoexfoliation glaucoma patients, and 21 control eyes without any type of glaucoma; all patients had co-existing cataract. Visual acuities, IOP, number of glaucoma medications used, anterior chamber depth (ACD), and gonioscopic evaluations were noted both pre- and postoperatively. Phacoemulsification and IOL implantations were performed via clear corneal incisions in the whole study group. Study group was followed-up for six months. Re sults: Postoperative visits at the 1st, 3rd, and 6th months were noted. After surgery, visual acuities improved significantly (p=0.001) in all groups. Intraocular pressures decreased in all groups postoperatively, but the change was statistically significant in the PACG group (p=0.013). Increase in ACD was significant in PACG group (p=0.001). Widening of iridocorneal angle and decrease in the number of antiglaucoma drugs were observed in all groups, but these were significant in the PACG group (p=0.001 and p<0.05, respectively). Dis cus si on: In glaucoma patients with co-existing cataract, phacoemulsification surgery allows both the visual rehabilitation and IOP control. This IOP lowering effect is seen most markedly in the PACG group. (Turk J Ophthalmol 2013; 43: 167-72)